Clinical case of an acute nonspecific parotitis at a newborn - Bochkova L.G.; Mikhryacheva V.V. (Саратовский научно-медицинский журнал, 2016)
This article presents a rare case of isolated parotid sialadenitis at a newborn. Possible etiology, classification, frequency, diagnosis and management of the disease are described in orderto determine this pathology. The paper gives the data on observation of a newborn with sialadenitis, the results of examination and treatment.